Exploration of two major boron transport genes BOR1 and NIP5;1 in the genomes of different plants - ÖZYİĞİT, İBRAHİM İLKER (TAYLOR & FRANCIS LTD, 2020)
Boron (B) is an essential plant micronutrient but studies regarding its transport are still limited to a few plants. This work identified two major B transport sequences in plants, NIP5;1 boric acid channel protein and BOR1 transporter. 80 BOR1 and 34 NIP5;1 homologs were identified in 18 different plant genomes. BOR1 homologs had a HCO3-transporter domain, 649-737 amino-acid residues with mainly basic nature, putative 8-11 transmembrane domains (TMDs) and 11-13 exons. NIP5;1 homologs had a MIP family domain, 294-311 amino-acid residues with basic nature, 5-6 putative TMDs and 3-5 exons. Tyrosine-based motif, acidic di-leucine motif and lysine residue, reported for polarity, vacuolar sorting and B-dependent degradation, were identified in BOR1 homologs. Two NPA motifs and an ar/R selectivity filter with AIGR residues, reportedly essential in B transport, were also found in NIP5;1 homologs. Two NPA motifs in AtNIP5;1 and OsNIP3;1 homologs were NPS and NPV, whereas in sequences homologous to AtNIP6;1 were NPA/V. Besides, ar/R selectivity filters were identified with A(N/S/T)IGR residues in NIP5;1 and NIP3;1 homologs. The BOR1 and NIP5;1 model structures were mainly conserved. Under different perturbations, Arabidopsis thaliana NIP5;1 and NIP6;1 genes demonstrated similar expression patterns although they act in different tissues, suggesting a common regulatory mechanism, whereas BOR1 showed a different expression pattern. BOR1 was substantially expressed in primary root, radicle and flower; NIP5;1 in primary root and roots, and NIP6;1 in petiole. NIP5;1, 6;1 and BOR1 expression in other plant organs implied their involvement in different pathways in addition to B uptake and its mobilization.
Keywords: Boric acid; orthologue; paralog; homolog; motif; selectivity filter; EFFLUX TRANSPORTER; INFLORESCENCE DEVELOPMENT; REPRODUCTIVE DEVELOPMENT; RHAMNOGALACTURONAN II; WIDE IDENTIFICATION; CROSS-LINKING; CELL-WALLS; ROLES; EXPRESSION; DEFICIENCY